Thoracolithiasis. (3rd January 2019) - Ogushi, Akihiko; Sugioka, Takashi; Nishiyama, Masanori
Abstract : Thoracoscopic image shows a thoracolith: its diameter was 13 mm and was soft and elastic, with a smooth surface. The core was black and was surrounded by yellow connective tissue. Given that mobility of the nodule is the key finding for the diagnosis, comparison with previous imaging studies is crucial.